Capacitive Deionization Using Alternating Polarization: Effect of Surface Charge on Salt Removal. (10th April 2017) - Gao, X.; Omosebi, A.; Holubowitch, N.; Landon, J.; Liu, K.
Graphical abstract: Highlights: Alternating polarization (AP) is tested with a capacitive deionization (CDI) stack. AP enhances CDI performance without the formation of inversion peaks. A maximum in salt adsorption capacity occurs halfway through the cycling test. The electrodes are oxidized during cycling to possess negative surface charge. Surface charge distribution is used to interpret salt removal resulting from AP. Abstract: Alternating polarization (AP) at ±1.2/0 V is performed on a capacitive deionization stack assembled with carbon xerogel (CX) electrodes. Long-term testing shows enhanced cycling stability without the formation of inversion peaks. AP also leads to an arch-shaped plot of salt adsorption capacity (SAC) versus cycling time, with the highest SAC of approximately 3 mg (NaCl) g −1 (CX) during this long-term test. Characterization of both the freshly prepared and cycled electrodes depict that AP results in surface charge of all the electrodes being modified from positive to negative character. By leveraging balances of electronic, surface, and ionic charges in carbon micropores, it is found that a portion of the electronic charge contributes to the ionic charge for salt adsorption, and another portion is parasitically consumed to balance the surface charge during the charge reconciliation process. When the consumption of electronic charge for charge reconciliation becomes minimal, both the positive and negative surface charges are nearly equivalent on the CX electrode. Under such a condition, the highest SAC values can be achieved for AP testing.